Smith, Hogan, and Ormerod's criminal law - Ormerod, David; Laird, Karl (Oxford University Press, 2018)
Rightly regarded as the leading doctrinal textbook on criminal law in England and Wales, this resource owes its consistent popularity to its accessible style, depth of analysis and breadth of coverage. Over 50 years since the publication of the first edition, Professor David Ormerod and Karl Laird continue the tradition set down by Professors Sir John Smith and Brian Hogan by producing a textbook of unrivalled quality